PERKAWINAN PADAGELAHANG DI BALI PERSPEKTIF ANTROPOLOGI - Kusmirayani, Luh Ayu (Humanis, 2013)
In line with the system of patrilineal kinship in Bali, where the lineage seen from the boys making the position a tad more special than girls. The most common form of marriage held in Bali is a regular marriage and nyentana. Nyentana marriage performed by a family that has no tad and so can not choose ordinary marriage. Then came the problems for families who have a child and do not allow choosing regular or nyentana marriage. This is where the emerging forms of marriage padagelahang considered as a solution to these problems. Problems in the study related to the background and impact of marriage padagelahang in Bali. The type of data used in the form of qualitative data with the primary and secondary data sources were obtained through observation, interviews and literature study. Analysis of the data used is descriptive qualitative analysis. Background padagelahang marriage was not merely because the same as an only child, but also because the same background as the child is not, by common soroh (clan) and by other factors. Marriage padagelahang this also cause a variety of effects in the family and society. The impact that the bride has dual status and the rights and obligations that also bear a double, given the status of husband and wife remain in their homes. Impact also on the marriage certificate and a letter of agreement.
Keywords: Marriage, Padagelahang, Padagelahang marriage.